O bambear semiótico no samba: da canção ao salão - Lacerda, Rachelina Sinfrônio de (2011)
The following work intends to investigate, through the Semiotics of Culture, united to literary-critical studies of MPB, the intersemiosis in the samba, more precisely, the inter-semiotic dialogue between two systems of distinct languages - the poetry of samba song (verbal language), and the samba ballroom (non-verbal language) -, from a synchronic analysis involving three choreographies mediated by the songs: Deixe Isso pra Lá (Alberto Paz and Edson Meneses) by João Sabiá (2007), Aquele Abraço (Gilberto Gil, 2000) and Pilotando o Bonde da Excursão (Marcelo D2, 2004). Such investigation will go of how this dance, understood as a modeling system of seconddegree (as well as the poetry), with an own code and endless combinatorial possibilities will can, in a choreographic representation, not just replicate the poetic system of the song, but modeled, in his own system, new insights and meanings in dialogue with the song. And, this way, contributing to mutual enrichment between the sign systems involved, creating a dynamic for change among languages that define the inventive character of culture in the samba.